Self-rated health is prospectively associated with uptake of screening for the early detection of colorectal cancer, not vice versa. Issue 4 (July 2016) - Neter, Efrat; Stein, Nili; Rennert, Gad; Hagoel, Lea
Abstract : Self-rated health (SRH) is a consistent predictor of mortality and other health outcomes. One of the mechanisms hypothesized to explain its validity as a predictor is that SRH affects the adoption of health behaviors. The present study examined the prospective association between SRH and performance of a recommended colorectal cancer (CRC) screening test. One thousand four hundred and seventy-six men and women aged 50–74 years, eligible for CRC screening, who had undergone the test a year before were interviewed 1–2 weeks (long interview, before testing) or 2 months (short interview, after testing) following the mailing of a test kit. Test performance was ascertained using an HMO's computerized data set. Respondents in the long interview group who rated their health as 'higher than others' performed the screening test 2 months following the invitation more than those who rated their health as similar to or lower than that of others (65.4, 61.6, and 49.1%, respectively, χ 2 =8.02, P =0.018). At the same time, these respondents perceived the risk of CRC as significantly lower than that of those who rated their health as comparable with or lower than that of others. In a multivariate logistic regression of CRC screening behavior that included demographic and perceptual variables, age, intentions, and SRH were found to be significant predictors. Among respondents in the short interview, who tested before the interview, there was no significant association between SRH and behavior. SRH prospectively predicts uptake of CRC screening better than other perceptual variables, after accounting for demographic variables.